2008
DOI: 10.1073/pnas.0708193105
|View full text |Cite
|
Sign up to set email alerts
|

Role of the familial Dutch mutation E22Q in the folding and aggregation of the 15–28 fragment of the Alzheimer amyloid-β protein

Abstract: Amyloid fibrils, large ordered aggregates of amyloid ␤ proteins (A␤), are clinical hallmarks of Alzheimer's disease (AD). The aggregation properties of amyloid ␤ proteins can be strongly affected by singlepoint mutations at positions 22 and 23. The Dutch mutation involves a substitution at position 22 (E22Q) and leads to increased deposition rates of the A␤E22Q peptide onto preseeded fibrils. We investigate the effect of the E22Q mutation on two key regions involved in the folding and aggregation of the A␤ pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 48 publications
(52 reference statements)
7
82
0
Order By: Relevance
“…FAD mutations can thus either inhibit or induce aggregation depending on the suitability of the replacing amino acid to accommodate an amyloidogenic or aggregated structure. Molecular dynamics simulations have suggested the depletion of the E22-K28 salt bridge to explain the enhanced aggregation of E22Q Ab , while the switch of a bend motif to a turn in the region Ab [22][23][24][25][26][27][28] could result in slower aggregation of the D23N Ab 1-42 mutant [25]. Overall fibril morphology is however not affected, as has been shown previously for a subset of FAD mutants [23].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…FAD mutations can thus either inhibit or induce aggregation depending on the suitability of the replacing amino acid to accommodate an amyloidogenic or aggregated structure. Molecular dynamics simulations have suggested the depletion of the E22-K28 salt bridge to explain the enhanced aggregation of E22Q Ab , while the switch of a bend motif to a turn in the region Ab [22][23][24][25][26][27][28] could result in slower aggregation of the D23N Ab 1-42 mutant [25]. Overall fibril morphology is however not affected, as has been shown previously for a subset of FAD mutants [23].…”
Section: Discussionmentioning
confidence: 69%
“…Alternatively, the denser peptide networks can be more prone to precipitation in the test tube which would lead to a similar observation. Although the effect of FAD-related mutations of Ab 1-42 on aggregation has been investigated in the past [23][24][25][26], no comprehensive study has been reported that directly compares the majority of the currently known mutations. Different Ab preparation methods and experimental conditions have led to considerable variation in reported effects of these mutations.…”
Section: Discussionmentioning
confidence: 99%
“…30 Our model of the folded Aβ(21-30) fragment satisfies all inter-proton constraints available from our previous NMR study. 9 It also readily explains the origin of the anomalously high hydrogen exchange protection factors observed for residues G25-K28 by Maggio and collaborators in fragments Aβ (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and Aβ . 31,32 Our simulations indicate that the amide hydrogens of these residues engage in hydrogen bonds with the side chain of D23 and thus get shielded from water.…”
Section: Resultsmentioning
confidence: 88%
“…The Glu22Gly/Gln/Lys mutations (Fig. 3A) do not directly affect the structure of the 22-28 loop but rather weaken the interactions between this loop and the central hydrophobic segment (amino acids 18 -21), as predicted by molecular dynamic simulations of the A␤ 15-28 Glu22Gln mutant, which increases the propensity of the ␤-structure in the hydrophobic segment (Baumketner et al, 2008).…”
Section: Mutations In A␤ 18 -41 Regionmentioning
confidence: 99%